Impact assessment of farm mechanization on potato production in Dadeldhura district, Nepal - Khadka, Kapil; Tiwari, Anupam; Yogi, Manju; Dhakal, Shiba Hari; Rijal, Ashok; Devkota, Kedar (Archives of Agriculture and Environmental Science, 2023)
Potato is one of the major cash crops in Nepal but farmers can’t maximize profits due to the low adoption of farm machinery and technology. There is insufficient research on agricultural mechanization and its effectiveness in the study area. Therefore, the goal of this study, which was carried out in the Dadeldhura district in 2022, was to assess the problem of farmers’ potato cultivation yielding less profit than they might have due to a lack of agriculture equipment and technology adoption. Purposive and simple random sampling were used to select 90 respondents from four local bodies of the Dadeldhura district. Primary data were collected from a household survey with a pre-tested semi-structured questionnaire and Key Informant Interview (KII). Secondary data were collected from annual PMAMP, MoALD, FAO reports, etc. MS Excel and SPSS (26.0) were used to analyze and interpret the collected data. The study divided farmers into groups based on whether they used bullocks or mini-tillers, and it found that mechanical power was mostly used during land preparation and irrigation phases. Fragmented land and lack of capital were major constraints to promoting mechanization. The study showed that mini-tiller users had a greater B: C ratio than bullock users. Similarly, the average variable cost of production per hectare was substantially lower in mini-tiller users than in bullock users. The results underlined the financial viability of mechanized potato farming and stressed the necessity of removing barriers to automation and developing regulations to support small-scale mechanization. The study concluded that mechanization might be extended beyond the stages of irrigation and field preparation to further improve cost-effectiveness and increase the profitability of potato cultivation for farmers in the Dadeldhura district. Overall, the study emphasized the necessity of strategic interventions to encourage automation and enhance the profitability of potato farming in the area.